Can Mindfulness Help to Alleviate Loneliness? A Systematic Review and Meta-Analysis - Teoh, Siew Li; Letchumanan, Vengadesh; Lee, Learn-Han (Frontiers in Psychology, 2021)
Objective: Mindfulness-based intervention (MBI) has been proposed to alleviate loneliness and improve social connectedness. Several randomized controlled trials (RCTs) have been conducted to evaluate the effectiveness of MBI. This study aimed to critically evaluate and determine the effectiveness and safety of MBI in alleviating the feeling of loneliness. Methods: We searched Medline, Embase, PsycInfo, Cochrane CENTRAL, and AMED for publications from inception to May 2020. We included RCTs with human subjects who were intervened with MBI with loneliness as an outcome. The quality of evidence was assessed using Cochrane's Risk of Bias (ROB) tool and GRADE. A random-effects model was used for meta-analysis. Results: Out of 92 articles identified, eight studies involving 815 participants were included in this study. Most (7/8) trials conducted a minimum of 8 weeks' MBI. Most of the trials (5/8) used UCLA-Loneliness Scale. A pooled analysis combining three trials and compared with wait-list showed significant improvement in loneliness score reduction using UCLA-R scale with MD of -6.33 (95% Confidence Interval (CI): -9.39, -3.26)). Subgroup analysis with only 2 Cognitively-Based Compassion Training (CBCT) trials also showed similar MD of -6.05 (95%CI: -9.53, 2.58). The overall quality of evidence (GRADE) was low. Conclusions: Mindfulness intervention with an average length of 8 weeks duration significantly improved the population's loneliness level with no mental health issue. However, this evidence had a low-GRADE level.